579 Work schedule and prospective antidepressant prescriptions in the swedish workforce: a 2-year study using national drug registry data. (24th April 2018) - Hall, AL; Kecklund, G; Leineweber, C; Tucker, P
Abstract : Introduction: Mood disorders affect millions of individuals worldwide and contribute to substantial morbidity and disability. A better understanding of modifiable work-related risk factors for depression could inform and advance prevention efforts in this area. This study used a large Swedish longitudinal occupational survey to prospectively examine the effect of self-reported work schedule on registry-based antidepressant prescriptions over a two-year period. Methods: The analytic sample (n=8643) was obtained from the Swedish Longitudinal Occupational Survey of Health. Sex-stratified and unstratified analyses were conducted using logistic regression. For exposure, 8 categories were used to describe work schedule in 2008: 'regular days' (3 categories: night work history=none, ≤3 years, or 4+years) 'night work (regular, rostered, or rotating)', 'regular shift work (no nights)', 'rostered work (no nights)', 'flexible/non-regulated hours', and 'other'. For the outcome, all prescriptions coded N06A according to the Anatomical Therapeutic Chemical System were obtained from the Swedish National Prescribed Drug Register and dichotomized into 'any' or 'no' prescriptions between 2008 and 2010. Estimates were adjusted for potential sociodemographic, health, and work confounders, and for prior depressive symptoms. Results: In unadjusted analyses, an increased odds ratio for depression was observed for 'Other' work hours in unstratified (OR=1.75, 95% CI: 1.21 to 2.51) and female (OR=1.62, 95% CI: 1.05 to 2.51) models; in adjusted models effects persisted but confidence intervals widened to non-significance at the p=0.05 level. In models adjusted for previous depressive symptoms, females in 'flexible/non-regulated' schedules showed an increased odds ratio for depression (OR=2.01, 95% CI: 1.08 to 3.76), while a decreased odds ratio was observed for the unstratified model 'regular shift work (no nights)' category (OR=0.61; 95% CI: 0.38 to 0.97). Discussion: This study's findings support prospective relationships between work schedule and antidepressant prescriptions in the Swedish workforce. Future research should continue to assess sex-stratified relationships, using detailed shift work exposure categories and objective registry data where possible.